پڕۆگرامێكی پێشنیازكراو بۆ بابەتى سۆڵفێجی گشتی بڕیارلێدراو بەسەر خوێندكارانی بەشی پەروە ردە ی هونەری – كۆلێجی پەروە ردە ی بنەڕە تی – زانكۆی سلێمانی - حسین, پ.ی.د.وفاء محمد; حسین, پ.د.جواد نعمت; محمود, تۆڵە ئومێد (Sulaimani Journal for Humanities, 2021)
The research aimed at preparing a proposed curriculum for General Solfege subject, in the field of music, for the students of University of Sulaimani, College of Basic Education, Department of Art Education. According the nature of the subject and the study objectives, didactic descriptive approach was adopted. The research population consisted of all subjects related to music in the curriculum of Department of Art Education during the academic year 2019-2020, namely: Theories of Music, General Solfege, Anthem and Song, History of Music, Piano Education, Piano's Main Instrument. The study sample is General Solfege and for this purpose, the researcher proposed a curriculum for General Solfege according to the producers and steps of the special model in designing educational proposed program after making use of two Models: Tyler and Hilda Taba. In the light of Integration Subjects Curriculum (ISC) and the suggestions and recommendations of the experts in the filed in art education and music, the study presented its conclusion in which General Solfege as an educational program for the students and as a guide for the lecturers was prepared.